Perception of the father about paternity in rooming-in-care - Márcia Rejane Strapasson; Beatriz Santana de Souza Lima; Gimerson Erick Ferreira; Gustavo Costa de Oliveira; Ana Lúcia de Lourenzi Bonilha; Potiguara de Oliveira Paz (Universidade Federal de Santa Maria, 2017)
Aim: to comprehend the parental perception about the father's support during the hospitalization of his wife and son in the rooming-in-care. Method: descriptive and exploratory qualitative approach, in the maternity of a private hospital inPorto Alegre. Semi-structured interviews were conducted with ten accompanying fathers, from September to October 2012. Results: from the analysis, two central categories that composed the discussion on the corpus emerged: "Understanding the meaning of being a father" and "The father as caregiver agent". In the investigated context, the perceptions of the parents about paternity showed that they sometimes do not identify themselves as potential care agents, although they feel prepared for it. Final thoughts: the study evidenced the need to implement humanization policies in the postpartum period, especially regarding the inclusion of fathers in the rooming-in, which would allow improvements in the parental bond and development of comprehensive health actions to the mother-father-child triad.